Study on Single Photon Imaging Method for Permanent Shadow Crater of the Moon - Z. Xia (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The detection of the permanent shadow area of the moon is currently a research hotspot. As the name suggests, there is no light in the permanent shadow area, and traditional methods cannot image it. This paper proposes a single photon imaging method that can be used for radiation imaging and distance imaging in this area. A spaceborne photon counting imaging system was designed, a mathematical model for photon counting was derived, and a Monte Carlo simulation method for photon counting process was proposed. The pulse laser echo waveform was simulated, and the radiation performance of the space photon counting imaging system was analysed. The simulated laser echo waveform has a high degree of restoration, indicating that the selected laser repetition rate and gating interval are appropriate. The echo waveforms of targets with the same reflectivity are similar but different, indicating that photon counting is a random process, which is consistent with reality. The higher the target reflectivity, the greater the total number of echo photons. Under the same reflectivity conditions, the total number of echo photons is different but similar. The relative radiation accuracy can reach 0.23%; The laser ranging accuracy can reach 0.075m. This study can provide theoretical basis and technical support for the design of space photon counting imaging systems and the adjustment of in orbit parameters.